2006
DOI: 10.1007/s11046-006-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota in poultry feeds and natural occurrence of aflatoxins, fumonisins and zearalenone in the Rio de Janeiro State, Brazil

Abstract: The intake of mycotoxin-contaminated feeds can lead to nutrient losses and may have adverse effects on animal health and on productivity. The aims of this study were (1) to determine the mycobiota present in poultry feed samples, and (2) to evaluate the natural occurrence of aflatoxin B(1), fumonisin B(1) and zearalenone. Fungal counts were similar between all culture media tested (10(3 )CFU g(-1)). The most frequent genus isolated was Penicillium spp. (41.26%) followed by Aspergillus spp. (33.33%) and Fusariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 32 publications
8
28
1
3
Order By: Relevance
“…Table 1 showed the frequency of isolated fungi genera in both private and commercial poultry feed samples, where a significant difference was obtained (X 2 = 199.818; P < 0.05 and X 2 = 237.053; P < 0.05) respectively, being the genus Aspergillus and Penicillium the most frequently isolated. This result is similar to the ones obtained by Rosa et al (2006), Oliveira et al (2006) and Figueroa et al (2009), who found that Aspergillus and Penicillium were the most frequently isolated genera in the poultry feed samples analyzed. Aspergillus has been shown to be predominant in cereals and other ingredients used in producing poultry feeds in the tropics as in the case of Nigeria (Pitt & Hocking, 1997;Makun et al, 2009).…”
Section: Resultssupporting
confidence: 91%
“…Table 1 showed the frequency of isolated fungi genera in both private and commercial poultry feed samples, where a significant difference was obtained (X 2 = 199.818; P < 0.05 and X 2 = 237.053; P < 0.05) respectively, being the genus Aspergillus and Penicillium the most frequently isolated. This result is similar to the ones obtained by Rosa et al (2006), Oliveira et al (2006) and Figueroa et al (2009), who found that Aspergillus and Penicillium were the most frequently isolated genera in the poultry feed samples analyzed. Aspergillus has been shown to be predominant in cereals and other ingredients used in producing poultry feeds in the tropics as in the case of Nigeria (Pitt & Hocking, 1997;Makun et al, 2009).…”
Section: Resultssupporting
confidence: 91%
“…This result is in agreement with the researches conducted by Dalcero et al (1997), Oliveira et al (2006), Rosa et al (2006), Krnjaja et al (2007) and Saleemi et al (2010), where they reported high levels of fungal contamination in feed. In this study, isolation frequency of different genera of contaminating fungi ranked in decreasing order; asperillus, rhizopus, mucor, yeast, dermatophyte, fusarium and penicillium which was in concordance with Saleemi et al (2010), Sivakumar et al (2014) and Bhuyan et al (2015).…”
Section: Discussionsupporting
confidence: 93%
“…In this study F. verticillioides was found as predominant followed by F. subglutinans. This prevalence has been informed from poultry feed in Latin America Magnoli et al 1998;Oliveira et al 2007). However, Argentinean samples always showed higher F. verticillioides isolation frequency than Brazilian samples.…”
Section: Discussionmentioning
confidence: 99%